Animated Series in the 90s, Between the Procedural Series and Serial: Format and Possible World of Spider-Man (1994-1998) - Encinas Cantalapiedra, Arturo; Morgado Gonçalves, Rodrigo Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The first contribution of the article is the delimitation of the fictional format of an animated series, Spider-Man (1994-1998), a procedural series with serial aspects. The second novelty is of a methodological nature, as it adds to the study of the format the mimesis of world, the object of study of the hermeneutics of possible worlds. In this way, it is understood that the recurring narrative elements in a series not only respond to production factors but also constitute the regularities that suggest the order and meaning of both the socially instituted world in the plot and the personal world of the protagonist.